A Consortium of Rhizosphere-Competent Actinobacteria Exhibiting Multiple Plant Growth-Promoting Traits Improves the Growth of Avicennia marina in the United Arab Emirates - El-Tarabily, Khaled A.; Sham, Arjun; Elbadawi, Alaa A.; Hassan, Amira H.; Alhosani, Bashaer K. K.; El-Esawi, Mohamed A.; AlKhajeh, Abdulmajeed S.; AbuQamar, Synan F. (Frontiers in Marine Science, 2021)
Grey mangrove (Avicennia marina) is the dominant vegetation along the coast of the United Arab Emirates (UAE). Despite acting as natural coastal guardians, little is known about the reforestation projects to increase mangrove cover over the years in the UAE and in the Arabian Gulf. Plant growth-promoting actinobacteria (PGPA) were isolated from mangrove rhizosphere sediments found in the UAE, and were evaluated for their potential to produce plant growth regulators and enhance mangrove growth under seawater irrigation conditions. In vitro screening identified nine rhizosphere-competent actinobacterial isolates in a naturally competitive environment, of which Streptomyces coelicoflavus (Sc) showed high phosphorus-solubilizing activity. Moreover, S. polychromogenes (Sp), S. bacillaris (Sb) and S. ferrugineus (Sf) produced of auxins, polyamines (PAs) and 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase, respectively. Although sediment inoculation with single isolates significantly improved dry biomass of mangrove shoots (43.2-74.0%) and roots (40.8-75.9%), the consortium of isolates (Sc/Sp/Sb/Sf) caused greater increase in dry weight of shoots (82.1%) and roots (81.6%) than with seawater-irrigated plants (control). In our greenhouse experiments, the levels of photosynthetic pigments, in planta auxins and PAs significantly increased in plant tissues inoculated with Sc/Sp/Sb/Sf; whereas ACC contents were reduced. This was also evident as the maximum velocity of rubisco carboxylation (Vcmax) increased four-fold in plants treated with the mixture of isolates over control. To the best of our knowledge, this is the first study reporting culturable halotolerant, rhizosphere-competent PGPA inhabiting salty and arid ecosystems applied individually or combined to promote mangrove growth under harsh conditions such as those found in the Arabian coastal areas.